A kind of degradable adhesive tape and preparation method thereof
By using biodegradable materials such as polylactic acid and starch to make tape, the problem of existing tape cannot be degraded is solved, and environmentally friendly, low-cost and high-performance degradable tape is achieved.
Patent Information
- Application Number
- CN202410957394.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-07-17
AI Technical Summary
The existing tape cannot be degraded, resulting in environmental pollution and waste of resources, and its recycling difficulties, increasing recycling costs.
The tape substrate and adhesive layer are made of fully biodegradable materials such as polylactic acid (PLA), starch, etc., and the degradable tape is made through specific preparation methods, including stirring, extrusion and blowing film, stretching and drying.
It achieves complete biodegradation of the tape, without pollution, simple process and low cost, improving the physical and degradation performance of the tape.
Smart Images

Figure CN118725758B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesive tapes, in particular to a degradable adhesive tape and a preparation method thereof. Background Art
[0002] With the increasing environmental protection requirements, the conventional common tapes made of materials such as polyvinyl chloride and polypropylene cannot be degraded. The existing treatment methods mainly include landfill and incineration. The problem with the landfill treatment method is that the degradation cycle of the existing common tapes in the soil is as long as several decades or even hundreds of years. The problem with the incineration treatment method is that it will cause pollution to the atmosphere.
[0003] In addition, although the production cost of this type of tape is low, the large-scale use of such tape will not only cause waste of resources, but also make it difficult to recycle packaging boxes with non-degradable tape, thereby increasing recycling costs.
[0004] Therefore, the adhesive tape made of completely biodegradable materials can be completely biodegradable, and can reduce the production cost of the adhesive tape, which is also an important way to improve the environment. In view of the above-mentioned existing problems, it is urgent to develop a completely biodegradable adhesive tape. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a degradable adhesive tape and a preparation method thereof, so as to solve the problem that the prior adhesive tape cannot be degraded as mentioned in the above technical background.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions:
[0007] In a first aspect, the present invention provides a degradable tape, comprising a degradable tape substrate layer and a degradable tape adhesive layer;
[0008] The degradable tape substrate layer comprises the following raw materials in parts by weight: 30-80 parts of polylactic acid (PLA), 20-30 parts of starch, 5-10 parts of distilled water, 0.5-10 parts of plasticizer, 1-2 parts of degradation agent, 0.1-1 parts of antioxidant, 0.1-1 parts of lubricant, and 0.2-0.4 parts of ultraviolet absorber;
[0009] The adhesive layer of the degradable tape contains the following raw materials in parts by weight: 40-50 parts of starch, 10-50 parts of polyvinyl alcohol, 35-40 parts of oxidant, 150-200 parts of water, 5-6 parts of sodium hydroxide, 2-4 parts of defoaming agent, 1-4 parts of cross-linking agent, 5-10 parts of acid, and 0.2-0.4 parts of aluminum sulfate.
[0010] As further preferred, the degradable tape substrate layer comprises the following raw materials in parts by weight: 50 parts of PLA, 20 parts of starch, 5 parts of distilled water, 2 parts of plasticizer, 1 part of degradation agent, 0.3 parts of antioxidant, 0.2 parts of lubricant, and 0.2 parts of ultraviolet absorber;
[0011] The adhesive layer of the degradable tape contains the following raw materials in parts by weight: 50 parts of starch, 30 parts of polyvinyl alcohol, 35 parts of oxidant, 160 parts of water, 5 parts of sodium hydroxide, 2 parts of defoaming agent, 1 part of cross-linking agent, 5-10 parts of acid, and 0.3 parts of aluminum sulfate; the specific amount of acid is determined based on adjusting the pH of the adhesive layer system to 5.5, and the usage range is 5-10 parts of acid.
[0012] As further preferred, in the degradable tape substrate layer, the polylactic acid (PLA) is selected from one or both of the American NatureWorks 4032D resin and 4060D resin;
[0013] The starch is one or more of tapioca starch, corn starch and potato starch;
[0014] The plasticizer is glycerol;
[0015] The degradation agent is one or more of a biodegradation agent and a photodegradation agent;
[0016] The antioxidant is 1010;
[0017] The lubricant is one of stearic acid and butyl stearate;
[0018] The ultraviolet absorber is UV-431.
[0019] As further preferred, in the adhesive layer of the degradable tape, the starch is one or more of cassava starch, corn starch and potato starch;
[0020] The oxidant is hydrogen peroxide;
[0021] The defoamer is tributyl phosphate;
[0022] The cross-linking agent is sodium trimetaphosphate;
[0023] The acid is glacial acetic acid.
[0024] In a second aspect, the present invention provides a method for preparing a degradable tape, specifically: first, separately prepare a degradable tape base layer and a degradable tape adhesive layer, then coat the degradable tape adhesive layer on the surface of the degradable tape base layer, dry and solidify, cool, and cut to obtain the degradable tape.
[0025] As a further preferred embodiment, a method for preparing a degradable tape comprises the following specific steps:
[0026] S1. Preparation of a degradable tape base layer: stirring a mixture containing polylactic acid (PLA), starch, distilled water and a plasticizer at 90° C. to 110° C. for 20 to 30 minutes, adding a degradation agent, an antioxidant, a lubricant and an ultraviolet absorber and stirring evenly to obtain a mixture;
[0027] Extruding the mixture into a blown film to obtain a semi-finished film; stretching and drying the semi-finished film; the temperature of the drying step is 160 to 180° C., and the drying time is 5 to 10 seconds to obtain a substrate layer;
[0028] S2. Preparation of the adhesive layer of the degradable tape: adding starch to water, stirring, and then adding an oxidant to carry out an oxidation reaction to obtain oxidized starch; adding the oxidized starch and polyvinyl alcohol to water, stirring and mixing, and then adding sodium hydroxide and a defoaming agent, continuing to stir, adding water and stirring again, and then adding a cross-linking agent and aluminum sulfate, stirring, and then adding an acid to adjust the pH value to obtain an adhesive layer;
[0029] S3. Preparation of degradable tape: Use a small coating machine with two rollers to transfer coat the adhesive layer on one side of the base material layer, dry it in an oven at a temperature of 80-90°C, and then roll it up and cut it after cooling.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The degradable adhesive tape of the present invention is degradable, pollution-free, has a simple process and is low in cost.
[0032] 2. The adhesive tape of the present invention has good degradability and physical properties under the synergistic effect of the components of the substrate layer and the adhesive layer. In particular, when the substrate layer is limited to polylactic acid (PLA) using American NatureWorks 4032D resin or 4060D resin, and the content of polylactic acid (PLA) is 30 to 80 parts, and the plasticizer is limited to propylene glycol, the resulting adhesive tape has more superior degradability and physical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a physical picture of the substrate layer obtained in Example 1;
[0034] Figure 2 This is a physical picture of the adhesive layer obtained in Example 1;
[0035] Figure 3 This is a real picture of the adhesive tape obtained in Example 1. DETAILED DESCRIPTION
[0036] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0037] As described in the background technology, the existing adhesive tape cannot be degraded. In order to solve the above technical problems, the present invention provides a method for preparing a degradable adhesive tape, which comprises: firstly preparing a degradable adhesive tape base layer and a degradable adhesive tape adhesive layer respectively, and then coating the degradable adhesive tape adhesive layer on the surface of the degradable adhesive tape base layer, drying and curing, cooling, and slitting to obtain the degradable adhesive tape.
[0038] The raw materials in the present invention, except for the following types, are all common materials on the market. Unless otherwise stated, no specific source manufacturer is specified.
[0039] American NatureWorks 4032D resin was purchased from Suzhou Tiantao Plastics Co., Ltd.;
[0040] ECO degradation agent E1000 was purchased from Ningbo Jiangbei Jinhua Trading Co., Ltd.;
[0041] Antioxidant 1010, purchased from Tianjin Lianlong New Materials Co., Ltd.;
[0042] Ultraviolet absorber UV-431 was purchased from Shanghai Fumao Chemical Co., Ltd.;
[0043] Total PLALX175 from Thailand was purchased from Shanghai Suge Plastic Technology Co., Ltd.
[0044] The degradable tape base layer comprises: stirring a mixture containing polylactic acid (PLA), starch, distilled water and a plasticizer at 90°C to 110°C for 20 to 30 minutes, adding a degradation agent, an antioxidant, a lubricant and an ultraviolet absorber and stirring evenly to obtain a mixture; the weight proportions of each component are as follows: 30 to 80 parts of polylactic acid (PLA); 20 to 30 parts of starch; 5 to 10 parts of distilled water; 0.5 to 10 parts of plasticizer; 1 to 2 parts of degradation agent; 0.1 to 1 part of antioxidant; 0.1 to 1 part of lubricant; 0.2 to 0.4 parts of ultraviolet absorber;
[0045] Extruding the mixture into a blown film to obtain a semi-finished film; stretching and drying the semi-finished film; the temperature of the drying step is 160 to 180° C., and the drying time is 5 to 10 seconds to obtain a substrate layer;
[0046] The polylactic acid (PLA) is selected from one or two of the American NatureWorks 4032D resin and 4060D resin; the starch is one or more of cassava starch, corn starch and potato starch; the plasticizer is glycerol; the degradation agent is one or more of a biodegradation agent and a photodegradation agent; the antioxidant is 1010; the lubricant is one of stearic acid and butyl stearate; the ultraviolet absorber is UV-431;
[0047] The adhesive layer of the degradable adhesive tape comprises: adding starch to water, stirring, and then adding an oxidant to carry out oxidation reaction to obtain oxidized starch; adding oxidized starch and polyvinyl alcohol to water, stirring and mixing, and then adding sodium hydroxide and a defoamer, continuing to stir, adding water and stirring again, and then adding a crosslinking agent and aluminum sulfate, stirring, and then adding acid to adjust the pH value to obtain an adhesive layer. The weight proportions of each component are as follows: 40-50 parts of starch, 10-50 parts of polyvinyl alcohol, 35-40 parts of oxidant, 150-200 parts of water, 5-6 parts of sodium hydroxide, 2-4 parts of defoamer, 1-4 parts of crosslinking agent, 5-10 parts of acid, and 0.2-0.4 parts of aluminum sulfate.
[0048] The starch is one or more of cassava starch, corn starch and potato starch; the oxidant is hydrogen peroxide; the defoamer is tributyl phosphate, the cross-linking agent is sodium trimetaphosphate, and the acid is glacial acetic acid;
[0049] A small coating machine is used to transfer coating with two rollers, and the adhesive layer is coated on one side of the substrate layer. The substrate layer is dried in an oven with the drying temperature controlled at 80-90°C. After drying and cooling, the substrate layer is rolled up and slit.
[0050] Example 1
[0051] This embodiment provides a degradable tape, and the preparation method thereof comprises:
[0052] S1. Preparation of substrate layer: Stirring a mixture of 50 parts of NatureWorks 4032D PLA, 20 parts of corn starch, 5 parts of distilled water and 2 parts of glycerol at 100° C. for 20 minutes, adding 1 part of degradation agent E1000, 0.3 parts of 1010, 0.2 parts of butyl stearate and 0.2 parts of UV-431 and stirring evenly to obtain a mixture; extruding the mixture and blowing film to obtain a semi-finished film; stretching and drying the semi-finished film; the temperature of the drying step is 170° C., and the drying time is 5 seconds, to obtain a substrate layer of 20 μm, such as Figure 1 As shown;
[0053] S2. Prepare an adhesive layer: add 50 parts of corn starch to 60 parts of water, stir to dissolve, then add 35 parts of 27% hydrogen peroxide to carry out oxidation reaction to obtain oxidized corn starch; add oxidized corn starch and 30 parts of polyvinyl alcohol to 40 parts of water, stir and mix at 40°C, then add 5 parts of 30% sodium hydroxide and 2 parts of tributyl phosphate, continue stirring for 30 minutes, add 60 parts of water and stir again for 30 minutes, then add 1 part of sodium trimetaphosphate and 0.3 part of aluminum sulfate, stir, and add glacial acetic acid to adjust the pH value to 5.5 (determine the specific amount of glacial acetic acid based on the adjustment of pH 5.5, and the use range is 5-10 parts of glacial acetic acid), and the adhesive layer is obtained. Figure 2 shown.
[0054] S3. Preparation of adhesive tape: Use a small coating machine with two rollers to transfer coating, coat the adhesive layer on one side of the substrate layer, the adhesive thickness is 15 μm, dry it in an oven, the drying temperature is controlled at 80°C, and then roll it up and cut it after drying and cooling. The obtained adhesive tape is as follows Figure 3 shown.
[0055] Example 2
[0056] This embodiment provides a degradable tape, and the preparation method thereof comprises:
[0057] S1. Prepare a substrate layer: stir a mixture of 80 parts of NatureWorks 4032D PLA, 30 parts of corn starch, 10 parts of distilled water and 2 parts of glycerol at 100° C. for 20 minutes, then add 1 part of degradation agent E1000, 0.3 parts of 1010, 0.2 parts of butyl stearate and 0.2 parts of UV-431 and stir evenly to obtain a mixture; extrude the mixture and perform film blowing to obtain a semi-finished film; stretch and dry the semi-finished film; the temperature of the drying step is 170° C., and the drying time is 5 seconds to obtain a 20 μm substrate layer;
[0058] S2. Prepare an adhesive layer: add 50 parts of corn starch to 60 parts of water, stir to dissolve, and then add 35 parts of 27% hydrogen peroxide to carry out oxidation reaction to obtain oxidized corn starch; add oxidized corn starch and 30 parts of polyvinyl alcohol to 40 parts of water, stir and mix at 40°C, then add 5 parts of 30% sodium hydroxide and 2 parts of tributyl phosphate, continue stirring for 30 minutes, add 60 parts of water and stir again for 30 minutes, then add 1 part of sodium trimetaphosphate and 0.3 parts of aluminum sulfate, stir, and add glacial acetic acid to adjust the pH value to 5.5 (determine the specific amount of glacial acetic acid based on the adjustment of pH 5.5, and the use range is 5-10 parts of glacial acetic acid), and the adhesive layer is obtained.
[0059] S3. Preparation of adhesive tape: Use a small coating machine with two rollers to transfer coat, coat the adhesive layer on one side of the base material layer, the adhesive thickness is 15 μm, dry in an oven, the drying temperature is controlled at 80°C, dry and cool, then roll up and slit.
[0060] Example 3
[0061] This embodiment provides a degradable tape, and the preparation method thereof comprises:
[0062] S1. Prepare a substrate layer: stir a mixture of 50 parts of NatureWorks 4032D PLA, 20 parts of corn starch, 5 parts of distilled water and 2 parts of glycerol at 100° C. for 20 minutes, then add 1 part of degradation agent E1000, 0.3 parts of 1010, 0.2 parts of butyl stearate and 0.2 parts of UV-431 and stir evenly to obtain a mixture; extrude the mixture and perform film blowing to obtain a semi-finished film; stretch and dry the semi-finished film; the temperature of the drying step is 170° C., and the drying time is 5 seconds, to obtain a substrate layer of 25 μm;
[0063] S2. Prepare an adhesive layer: add 50 parts of corn starch to 60 parts of water, stir to dissolve, and then add 35 parts of 27% hydrogen peroxide to carry out oxidation reaction to obtain oxidized corn starch; add oxidized corn starch and 30 parts of polyvinyl alcohol to 40 parts of water, stir and mix at 40°C, then add 5 parts of 30% sodium hydroxide and 2 parts of tributyl phosphate, continue stirring for 30 minutes, add 60 parts of water and stir again for 30 minutes, then add 1 part of sodium trimetaphosphate and 0.3 parts of aluminum sulfate, stir, and add glacial acetic acid to adjust the pH value to 5.5 (determine the specific amount of glacial acetic acid based on the adjustment of pH 5.5, and the use range is 5-10 parts of glacial acetic acid), and the adhesive layer is obtained.
[0064] S3. Preparation of adhesive tape: Use a small coating machine with two rollers to transfer coat, coat the adhesive layer on one side of the base material layer, the adhesive thickness is 15 μm, dry in an oven, the drying temperature is controlled at 80°C, dry and cool, then roll up and slit.
[0065] Example 4
[0066] This embodiment provides a degradable tape, and the preparation method thereof comprises:
[0067] S1. Prepare a substrate layer: stir a mixture of 30 parts of NatureWorks 4032D PLA, 20 parts of corn starch, 5 parts of distilled water and 2 parts of glycerol at 100° C. for 20 minutes, then add 1 part of degradation agent E1000, 0.3 parts of 1010, 0.2 parts of butyl stearate and 0.2 parts of UV-431 and stir evenly to obtain a mixture; extrude the mixture and perform film blowing to obtain a semi-finished film; stretch and dry the semi-finished film; the temperature of the drying step is 170° C., and the drying time is 5 seconds, to obtain a 20 μm substrate layer;
[0068] S2. Prepare an adhesive layer: add 45 parts of corn starch to 55 parts of water, stir to dissolve, then add 35 parts of 27% hydrogen peroxide to carry out oxidation reaction to obtain oxidized corn starch; add oxidized corn starch and 30 parts of polyvinyl alcohol to 40 parts of water, stir and mix at 40°C, then add 5 parts of 30% sodium hydroxide and 2 parts of tributyl phosphate, continue stirring for 30 minutes, add 60 parts of water and stir again for 30 minutes, then add 1 part of sodium trimetaphosphate and 0.3 parts of aluminum sulfate, stir, and add glacial acetic acid to adjust the pH value to 5.5 (determine the specific amount of glacial acetic acid based on the adjustment of pH 5.5, and the use range is 5-10 parts of glacial acetic acid), and the adhesive layer is obtained.
[0069] S3. Preparation of adhesive tape: Use a small coating machine with two rollers to transfer coat, coat the adhesive layer on one side of the base material layer, the adhesive thickness is 15 μm, dry in an oven, the drying temperature is controlled at 80°C, dry and cool, then roll up and slit.
[0070] Example 5
[0071] This embodiment provides a degradable tape, and the preparation method thereof comprises:
[0072] S1. Prepare a substrate layer: stir a mixture of 50 parts of NatureWorks 4032D PLA, 20 parts of corn starch, 5 parts of distilled water and 2 parts of glycerol at 100° C. for 20 minutes, then add 1 part of degradation agent E1000, 0.3 parts of 1010, 0.2 parts of butyl stearate and 0.2 parts of UV-431 and stir evenly to obtain a mixture; extrude the mixture and perform film blowing to obtain a semi-finished film; stretch and dry the semi-finished film; the temperature of the drying step is 170° C., and the drying time is 5 seconds to obtain a 20 μm substrate layer;
[0073] S2. Prepare an adhesive layer: add 40 parts of corn starch to 50 parts of water, stir to dissolve, then add 35 parts of 27% hydrogen peroxide to carry out oxidation reaction to obtain oxidized corn starch; add oxidized corn starch and 30 parts of polyvinyl alcohol to 40 parts of water, stir and mix at 40°C, then add 5 parts of 30% sodium hydroxide and 2 parts of tributyl phosphate, continue stirring for 30 minutes, add 60 parts of water and stir again for 30 minutes, then add 1 part of sodium trimetaphosphate and 0.3 parts of aluminum sulfate, stir, and add glacial acetic acid to adjust the pH value to 5.5 (determine the specific amount of glacial acetic acid based on the adjustment of pH 5.5, and the use range is 5-10 parts of glacial acetic acid), and the adhesive layer is obtained.
[0074] S3. Preparation of adhesive tape: Use a small coating machine with two rollers to transfer coat, coat the adhesive layer on one side of the base material layer, the adhesive thickness is 15 μm, dry in an oven, the drying temperature is controlled at 80°C, dry and cool, then roll up and slit.
[0075] Comparative Example 1
[0076] A commercially available 20 μm thick BOPP (biaxially oriented polypropylene) film with a single-sided corona on the inside (Guangdong Weifu Packaging Materials Co., Ltd.) was used as the substrate, and a commercially available acrylic water-based adhesive (thickness 15 μm, Dongguan Wanjiang Jianda Adhesive Products Co., Ltd. HM3808) was coated on the corona surface without back coating a release layer. The film then entered a drying oven at a temperature of 110°C to obtain a comparative sample.
[0077] Comparative Example 2
[0078] The existing degradable tape (Dongguan Nabai) has a substrate layer prepared from a PBAT / PLA blend and plasticizer epoxidized soybean oil to obtain a 20 μm thick film, and an adhesive layer synthesized from polyethylene glycol and dichlorodiphenyl sulfone. The adhesive layer is coated on one side of the substrate layer using a two-roll transfer coating method using a small coating machine. The adhesive layer has a thickness of 15 μm and is dried using an infrared drying method. The drying temperature is controlled at 50-60°C, and then the film is rolled up and slit after drying and cooling to obtain a comparative sample.
[0079] Comparative Example 3
[0080] A comparative example sample was obtained by replacing an equal amount of NatureWorks 4032D PLA in Example 1 with Thailand Total PLA LX175.
[0081] Comparative Example 4
[0082] The number of NatureWorks 4032D PLA in Example 1 was changed from 50 parts to 25 parts, and the other parts were the same as those in the example to obtain a comparative example sample.
[0083] Comparative Example 5
[0084] The number of NatureWorks 4032D PLA in Example 1 was changed from 50 to 85, and the other parts were the same as those in the example to obtain a comparative example sample.
[0085] Comparative Example 6
[0086] A comparative example sample was obtained by replacing an equal amount of glycerol in Example 1 with soybean oil.
[0087] The performance testing method of the degradable tape involved in the present invention is as follows:
[0088] 1. 180° peel strength under normal conditions: tested in accordance with national standard GB / T2792.
[0089] 2. 180° peel strength after wet heat aging: Place the tape in a constant temperature and humidity chamber at a temperature of (60±2)℃ and a relative humidity of (80±5)% for 24 hours. Immediately after taking it out, test it in accordance with the national standard GB / T2792 and complete the test within 3 minutes.
[0090] 3. 180° peel strength after low temperature treatment: Place the tape in a constant temperature box at (-20±2)℃ for 4 hours, take it out and immediately test it according to GB / T2792 national standard, and complete the test within 3 minutes.
[0091] 4. Initial adhesion: Tested according to the test method specified in Method A of GB / T4852-2002, with an inclination angle of 30°.
[0092] 5. Adhesion: The test is conducted in accordance with the test method specified in Method A of the national standard GB / T4851-2014. The width of the tape is (24±0.5) mm, the length of the adhesive surface of the tape on the steel plate of the test platform is (12±0.5) mm, and the mass of the weight is (1000±5) grams.
[0093] 6.Tensile strength under normal conditions: Tested at room temperature of 23°C in accordance with national standard GB / T30776-2014 method A.
[0094] 7. Tensile strength after wet heat aging: Place the tape in a constant temperature and humidity chamber at a temperature of (60±2)°C and a relative humidity of (80±5)% for 24 hours. After taking it out, immediately test it in accordance with the national standard GB / T30776-2014 method A and complete the test within 3 minutes.
[0095] 8. Tensile strength after low temperature treatment: Place the tape in a constant temperature box at (-20±2)℃ for 4 hours. After taking it out, immediately test it according to the national standard GB / T30776-2014 method A and complete the test within 3 minutes.
[0096] 9. Low-speed unwinding force: tested at room temperature of 23°C in accordance with national standard GB / T4850.
[0097] 10. Solvent residue limit: Test according to the method specified in 6.6.17 of national standard GB10004-2008.
[0098] 11.Limits of heavy metals and specific substances: After the tape samples are digested by a high-pressure microwave system, they are tested by an atomic absorption spectrometer in accordance with the method specified in the national standard GB / T15337.
[0099] 12. Biodegradability: The inorganic component (volatile solid content) is tested in accordance with the provisions of national standard GB / T9345.1 method A, and the test temperature is 650°C. The biodegradability is tested in accordance with the provisions of national standards GB / T19277.1, GB / T19277.2, GB / T19276.1 and GB / T19276.2. During arbitration, the biodegradability is tested in accordance with national standard GB / T19277.1.
[0100] 13. Maximum heat-resistant temperature: Put 700mL of distilled water in a 1L glass beaker, stir with a magnetic stirrer at 100 rpm, control the water temperature to 20, 30, 40, 50, 60, 70, 80, and 90°C respectively, take a 10mm wide tape, cut a 10cm length, and put it into the distilled water of different temperatures. The temperature corresponding to the tape not breaking or dissolving within 10 minutes is the maximum heat-resistant temperature.
[0101] 14. Dissolution time: Place 700 mL of distilled water in a 1 L glass beaker, stir with a magnetic stirrer at 100 rpm, control the water temperature at 30±2°C, place a 10 mm wide and 10 cm long tape in the distilled water, and gradually break the tape until the particle size of the fragments is less than 1 mm. The corresponding time is the water dissolution time of the tape.
[0102] The tape test results are shown in Table 1 and Table 2:
[0103] Table 1
[0104]
[0105] Table 2
[0106]
[0107] The adhesive tape of Comparative Example 1 prepared with commercially available BOPP film and acrylic acid ester water-based pressure-sensitive adhesive cannot be dissolved in water and cannot be completely degraded. However, the adhesive tape samples prepared in Examples 1 to 5 have substrates and adhesive layer materials that can be dissolved in water and are biodegradable. The adhesive tapes prepared in Examples 1 to 5 of the present invention are superior to the degradable adhesive tape of Comparative Example 2 in terms of degradation performance and physical properties.
[0108] Comparison between Examples 1 and 2 and Comparative Examples 4 and 5 shows that the tape sample in accordance with the present invention can be obtained by limiting the PLA to the preferred range of the present application (30 to 80 parts of polylactic acid PLA), otherwise the degradation performance and physical properties of the tape will be affected. Comparison between Examples 1 and 3 shows that increasing the thickness of the substrate layer is beneficial to improving the mechanical properties of the tape and the water resistance of the tape, but has no effect on the biodegradability and only causes a longer water dissolution time.
[0109] By comparing Example 1 and Comparative Example 3, it can be seen that limiting PLA to the preferred grades of the present application (American NatureWorks 4032D resin, 4060D resin) can obtain a tape with better degradation performance and physical properties, while other grades will reduce the degradation performance and physical properties of the tape.
[0110] By comparing Example 1 and Comparative Example 6, it can be seen that by limiting the plasticizer of the substrate layer to the preferred range of the present application (propylene glycol), a tape with better degradation performance and physical properties can be obtained, while other plasticizers will reduce the degradation performance and physical properties of the tape.
[0111] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A degradable tape, characterized in that: It comprises a degradable tape substrate layer and a degradable tape adhesive layer; The degradable tape substrate layer comprises the following raw materials in parts by weight: 30-80 parts of PLA, 20-30 parts of starch, 5-10 parts of distilled water, 0.5-10 parts of plasticizer, 1-2 parts of degradation agent, 0.1-1 parts of antioxidant, 0.1-1 parts of lubricant, and 0.2-0.4 parts of ultraviolet absorber; The adhesive layer of the degradable tape comprises the following raw materials in parts by weight: 40-50 parts of starch, 10-50 parts of polyvinyl alcohol, 35-40 parts of oxidant, 150-200 parts of water, 5-6 parts of sodium hydroxide, 2-4 parts of defoaming agent, 1-4 parts of cross-linking agent, 5-10 parts of acid, and 0.2-0.4 parts of aluminum sulfate; In the degradable tape substrate layer, the polylactic acid (PLA) is American NatureWorks 4032D resin; The starch is one or more of tapioca starch, corn starch and potato starch; The plasticizer is glycerol; The degradation agent is one or more of a biodegradation agent and a photodegradation agent; The antioxidant is 1010; The lubricant is one of stearic acid and butyl stearate; The ultraviolet absorber is UV-431.
2. A degradable tape according to claim 1, characterized in that: The degradable tape substrate layer comprises the following raw materials in parts by weight: 50 parts of PLA, 20 parts of starch, 5 parts of distilled water, 2 parts of plasticizer, 1 part of degradation agent, 0.3 parts of antioxidant, 0.2 parts of lubricant, and 0.2 parts of ultraviolet absorber; The adhesive layer of the degradable tape contains the following raw materials in parts by weight: 50 parts of starch, 30 parts of polyvinyl alcohol, 35 parts of oxidant, 160 parts of water, 5 parts of sodium hydroxide, 2 parts of defoaming agent, 1 part of cross-linking agent, 5-10 parts of acid, and 0.3 parts of aluminum sulfate.
3. A degradable tape according to claim 2, characterized in that: In the adhesive layer of the degradable tape, the starch is one or more of cassava starch, corn starch and potato starch; The oxidant is hydrogen peroxide; The defoamer is tributyl phosphate; The cross-linking agent is sodium trimetaphosphate; The acid is glacial acetic acid.
4. A method for preparing a degradable adhesive tape according to any one of claims 1 to 3, characterized in that: Firstly, a degradable tape substrate layer and a degradable tape adhesive layer are prepared respectively, and then the degradable tape adhesive layer is coated on the surface of the degradable tape substrate, dried and solidified, cooled and slit to obtain the degradable tape.
5. The method for preparing a degradable adhesive tape according to claim 4, characterized in that: The specific steps include: S1. Preparation of a degradable tape base layer: stirring a mixture containing polylactic acid (PLA), starch, distilled water and a plasticizer at 90° C. to 110° C. for 20 to 30 minutes, adding a degradation agent, an antioxidant, a lubricant and an ultraviolet absorber and stirring evenly to obtain a mixture; Extruding the mixture into a blown film to obtain a semi-finished film; stretching and drying the semi-finished film; the temperature of the drying step is 160 to 180° C., and the drying time is 5 to 10 seconds to obtain a substrate layer; S2. Preparation of the adhesive layer of the degradable tape: adding starch to water, stirring, and then adding an oxidant to carry out an oxidation reaction to obtain oxidized starch; adding the oxidized starch and polyvinyl alcohol to water, stirring and mixing, and then adding sodium hydroxide and a defoaming agent, continuing to stir, adding water and stirring again, and then adding a cross-linking agent and aluminum sulfate, stirring, and then adding an acid to adjust the pH value to obtain an adhesive layer; S3. Preparation of degradable tape: Use a small coating machine with two rollers to transfer coat the adhesive layer on one side of the base material layer, dry it in an oven at a temperature of 80-90°C, and then roll it up and cut it after cooling.
Citation Information
Patent Citations
Starch-based adhesive and preparation method thereof
CN108641622A
Preparation method of PLA-based degradable adhesive tape
CN113980598A
Cited By
Preparation method of full-bio-based degradable environment-friendly adhesive tape
CN121873693A